упростите выражения:
3а(а+1)+(а+2)(а-3)
(у-3)(5-у)-(4-у)(у+6)
преобразуйте в многочлен:
3х(3х+7)-(3х+1)все во второй степени
2
(у-4) -(4-у)(4+у)
пожалуста помоги
Ответы
3а(а+1)+(а+2)(а-3)=
= 3а(2 степень) + 3а + а(2 степень) - 6 =
= 4 а( 2степень) + 3а - 6
__________________________________
(у-3)(5-у)-(4-у)(у+6)=
= у(2степень)-15+24-у(2степень)=
= 15-24=
= -9
__________________________________
3х(3х+7)-(3х+1) =
= 9х(2 степень)(3х+1)+ 21 х (3х+1)=
=27 х(3 степень) + 9х + 63 х + 21 х
___________________________________
(у-4)-(4-у)(4+у)=
= 0
3а(а+1)+(а+2)(а-3)=
= 3а(2 степень) + 3а + а(2 степень) - 6 =
= 4 а( 2степень) + 3а - 6
(у-3)(5-у)-(4-у)(у+6)=
= у(2степень)-15+24-у(2степень)=
= 15-24=
= -9
3х(3х+7)-(3х+1) =
= 9х(2 степень)(3х+1)+ 21 х (3х+1)=
=27 х(3 степень) + 9х + 63 х + 21 х
(у-4)-(4-у)(4+у)=
= 0